The stability of β-carotene in vitamin-enriched flour foods - Sabino, Myrna (1979)
A spectrophotometric method was employed for determining th e B-carotene content of 100 vitamin-added samples of flour foods of which 50 samples were sernolí na faods and 50 samples of egg-added f'lour foods. Possible in terfuring substances were investigated by ascending papel' chrorna tog raphy. The results obtained indicated a loss of B-carotene due to boiling which amounted to 74% and 37% respec tively, for the semolina mass and th e "egg-added flour food". It isconcluded that the main role of B-carotene in these products was to act as a dye rather than as p ro-vitarnin A.